Detection of Malaria Parasites in donated blood in Zimbabwe using the rapid SD Bioline test kit. - Samakande, Danai; Mandisodza, Arthur; Chikwasha, Vasco; Mavenyengwa, Rooyen; Mavunganidze, George; Parirewa, Judith (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The potential of transfusion transmitted malaria infection in Zimbabwe is highbecause blood donors are not screened for malaria infection. The study was carried out toassess possible malaria infection in blood donors from malaria endemic regions using therapid and routine microscopy methods. Experts repeated the microscopy method onsamples that were positive with the rapid SD Bioline immunochromatography method. All blood donors were negative for malaria using the conventional thin and thickblood film methods. Eight (4.5%) blood donors were positive using the SD Biolineimmunochromatography method. Repeats of the microscopy tests on eight positive SDBioline results by experts were negative. Bulawayo, Zimbabwe’s second largest city, hadthe highest malaria positive donor blood. There was an association between malariainfection and Rh D positive blood donors. It can be concluded that screening blood donors for malaria using more sensitivetechniques is necessary to avoid transfusion-transmitted malaria infection.